Análise molecular do gene WWOX no carcinoma de células escamosas da cavidade bucal - Flavio Juliano Garcia Santos Pimenta (2005)
Oral squamous cell carcinoma (OSCC) is the most common malignant neoplasm of the oral cavity, representing approximately 90% of all oral carcinomas. It is acknowledged that oral carcinogenesis is a multi-step process of accumulated genetic damage, such as activation of oncogenes, tumor suppressor genes inactivation, and loss of heterozygosity at numerous chromosomal locations. However, the specific molecular mechanisms involved in OSCC tumorigenesis have not yet been completely elucidated. The WWOX gene is a candidate tumor suppressor gene located at 16q23.3-24.1, spanning the second most common fragile site, FRA16D. Alterations of this gene have been demonstrated in multiple types of cancer, including lung and esophageal squamous cell carcinoma, which share some predictive factors with OSCCs. To evaluate the role of the WWOX gene in OSCC, we analyzed 20 tumors and 10 normal oral mucosas. RNA transcription was altered in 35% of tumors, with complete absence of transcripts as well as absence of exons 6-8, exon 7, exons 6-8 and partial loss of exons 8 and 9. To determine if the aberrant transcripts were translated, Western blots were carried out; however only the normal protein was detected. Immunohistochemistry showed a reduction in WWOX protein expression affecting 40% of tumors when compared with normal mucosa. In addition, a novel somatic mutation (S329F) was found. The presence of alterations in mRNA transcription correlated with the reduced expression of WWOX protein in the tumors. These results show that WWOX gene is frequently altered in OSCC and may contribute to the carcinogenesis processes in oral cancer.